Uzbekistan - Lerner Publications Company. Geography Dept. (Minneapolis : Lerner, 1993)
Discusses the topography, location, ethnic mixture, history, and current political situation of the former Soviet republic of Uzbekistan.
Includes index.
Child Study Children's Book Committee.
Wilson's Children.
Wilson's Junior High School.
7.1
4-6
Keywords: Uzbekistan -- Juvenile literature; Uzbekistan; Uzbekistan